2019
DOI: 10.20517/2394-5079.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Advances in early diagnosis of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most recurrent hepatic malignancy and the third in the cancer-related casualties in the west. The frequently-documented causes of HCC are chronic liver infections by hepatitis B virus or hepatitis C virus, nonalcoholic fatty liver disease, cirrhosis, exposure to aflatoxins and tobacco smocking, etc. Clinical presentation of this fatal disease ranges from asymptomatic to upper abdominal pain or common health conditions like weight loss or lethargy. Among current surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Analysis of the microarray data has also indicated the downregulation of miR-4270 expression in HCC patients compared to the non-tumor tissues [ 9 ] . It is worth mentioning that HCC has various etiologies, such as non-alcoholic fatty liver disease, alcoholic liver disease, and different viral hepatitis, leading to tumorigenesis [ 3 , 24 ] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the microarray data has also indicated the downregulation of miR-4270 expression in HCC patients compared to the non-tumor tissues [ 9 ] . It is worth mentioning that HCC has various etiologies, such as non-alcoholic fatty liver disease, alcoholic liver disease, and different viral hepatitis, leading to tumorigenesis [ 3 , 24 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Little data are known about the mechanism of action of miRNAs on HCC pathogenesis [ 3 , 10 , 24 , 25 ] . In this regard, we suggested that miRNAs played role through different mechanisms in various cell lines of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) is one of the most common primary liver tumors in the world. It is characterized by high morbidity, rapid growth, strong invasion and high mortality [1][2][3]. Surgery is the most common method of treatment of liver cancer, but it is not appropriate for most HCC patients present with advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…It is really difficult to diagnose HCC early on. Hope for an early HCC diagnosis is provided by recent technical developments 5 .…”
mentioning
confidence: 99%